Left Bundle Branch Pacing: procedural outcomes using different sheaths. (19th May 2022) - Marcantoni, L; Centioni, M; Pastore, G; Manzato, E; Fornasaro, M; Cappato, E; Pigaiani, C; Marsiglia, S; Baracca, E; Zanon, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left Bundle Branch Pacing (LBBP) ensures physiologic ventricular activation. Growing experiences are rising on its applicability . Different tools available allow successful implant in different cardiac anatomies. Objective: To analyse implant success rate and acute electrical parameters in LBBP guided by C315 fixed curve sheath or Selectra3D sheath. Methods: 151 patients (mean age 79.8±8.3 years; 51% males) received LBBP. Pacing indication: AV block 50%, SND 12%, slow AF12%, ablate&pace 9%; HF 14%, revision of previous lead 1%. Coronary disease was present in 31%; hypertension in 93%, diabetes in 30%, severe valvular disease in 5%, persistent AF in 31% pts. Average QRS duration was 136±34 ms. Basal mean EF 52±12%. Different criteria for successful LBBP were analyzed (table 1). Results: The lead was successfully implanted in the left bundle in 97.3% pts. In 60.5% pts guided by the C315 Medtronic fixed curve sheath while in 39.5% pts by the Selectra3D (40-S, 55-M, 65-L) Biotronik sheaths. 93 (63%) pts received 3830 fixed screw lead, 51 (35%) pts received Solia S 60 stylet-driven lead and 3 (2%) patients received Tendril 58 cm stylet-driven lead. All different criteria analysed to define successful LBBP were comparable in the C315 and Selectra 3D group (table 1). In 61% pts LBBP was the first choice, in 39% LBBP was aimed after unsatisfactory HBP (His threshold>2V or paced QRS>140 ms). The LBBP lead was connected to the RV port in 67% DR and 18% SR PMs; to the LV port in the 22 CRT devices. Mean fluoroscopy time was 10±6 min including implant of all leads, without differences between implants. Electrical parameters were highly favourable in all patients (mean threshold 0.73±0.27V and mean sensing 11±5.8 mV) without differences between the 2 sheaths. Pacing impedance was significantly lower in the Selectra 3D group. Paced QRS duration was 114±15 ms (112±14 vs 116±16 ms; P 0.180). Implant failure were 4 (2 due to severe tricuspid regurgitation and 2 to severe dilated atria). Conclusion: LBBP is highly reliable in clinical practice. The different sheath available lead to successfully perform the implant in different cardiac anatomies. In our experience there was no differences in technical acute outcome between implant guided by C315 Medtronic sheath and Selectra3D Biotronik sheath.